Mendalami Informasi dengan Bertabayyun Menurut Al-Qur’an di Tinjau Dari Tafsir Klasik dan Kontemporer - Sulhi M. Daud Abdul Kadir; Sahrizal Vahlepi (Universitas Batanghari Jambi, 2021)
today social media is an effective, transparent and efficient communication medium. the approach used in this research is a qualitative approach, with the type of research library research. The primary data sources in this study are the books of commentary (Ibn Jarir Ath-Thobari, Ibn Kathir, Al-Misbah, and Al-Azhar) and secondary data on theses, journals, and articles that discuss tabayyun, as well as dictionaries, and books related to tabayyun. which is relevant. The results of this study conclude that according to various opinions of mufassir from classical and contemporary circles, namely 1) There is a prohibition on hasty in taking action on a news 2) Fasiq is a liar and makes mistakes or is damaged. 3) Every news must be filtered so that they do not step or act in an unnatural situation. 4) The information that comes is not justified or rejected, but the truth must be investigated first